Cardiorespiratory Fitness in Pediatric Renal Transplant Recipients - Sethna, C.B. (2009)
BACKGROUND: The impact of body size, fat-free mass (FFM) and fat mass (FM) on cardiorespiratory fitness in pediatric renal transplant recipients (TX) has not been established. Study objectives were to assess maximal oxygen consumption (VO(2max)) in TX and controls, adjusted for body composition, and to identify risk factors for reduced fitness in TX. METHODS: Cycle ergometry and DXA were obtained in 50 TX and 70 controls, ages 8 to 21 yr. Control recruitment was targeted to include obese subjects with body mass index (BMI) Z-scores comparable to TX. Allometric regression models were utilized. RESULTS: TX had significantly lower height Z-scores (p < 0.001) and comparable BMI Z-scores. VO(2max) per body weight (ml/kg/min) and per FFM (ml/kgFFM/min) did not differ between groups. However, VO(2max) was 13% lower (95% CI 18, 8; p < 0.001) in TX, compared with controls, adjusted for FM, FFM, sex and race. Greater FFM, lower FM, non-black race, and male sex were independently associated with greater VO(2max.) Within TX, hemoglobin levels were positively associated with VO(2max) (p = 0.04) and sirolimus use was associated with lower VO(2max) (p < 0.01). CONCLUSIONS: TX had significant VO(2max) deficits that were not captured by conventional measures (ml/kg/min). Greater FM was an independent risk factor for low VO(2max). Lower fitness in TX may be related to sirolimus effects on skeletal muscle.